Perlindungan Hukum Terhadap Istri Atas Suami Yang Berpoligami Tanpa Persetujuan Istri dan Pengadilan - Vina Fadila Hasna Raehany (Dinasti Research, 2025)
Marriage in Indonesia based on the principle of monogamy, as written in Law Number 1 of 1974 concerning Marriage which emphasizes that a man can only have one wife, as well as a woman can only have one husband. However, there is an exception that a husband can have more than one wife on the condition that he has permission from the Court and is indeed desired by the parties concerned, and the act must have a consent from the first wife. There are still irregularities that occur in the practice of polygamy, one of them is a secret polygamous marriage carried out by a man with a woman apart from his wife without the consent of the legal wife and without the permission of the Religious Court, as happened in Decision Number 1106/Pdt.G/2024/PA.Cbn. The research method uses in this article is qualitative normative by referring to applicable regulations and doctrines with case study approach and the data collection is based on document studies. The result is that polygamous marriage carried out without the permission of the first wife and the Religious Court are invalid and null and void, which results in the second marriage being considered unprecedented. The legal protection for the first wife can be various, such as the application for annulment of the second marriage submitted by the first wife and also even if indications of fraud are found in the implementations of marriage to the Office of Religious Affairs, the first wife can report it and the parties involved can be subject to criminal sanctions.